Exchange rates and fundamentals: Forecasting with long maturity forward rates - Darvas, Zsolt; Schepp, Zoltán (Journal of international money and finance, 2024)
•The unobserved expected future exchange rate is eliminated from a theoretical model.•The long-maturity forward exchange rate is a proxy for exchange rate disequilibrium.•A new error correction model leads to unprecedented forecasting results.•Both short-horizon and long-horizon out-of-sample predictability is achieved.•The model is simple, linear, easy to replicate, and uses real-time available data. We show that in a popular model of exchange rate determination, the unobserved expected future exchange rate can be substituted with the observed forward exchange rate. This allows the derivation of a new error-correction forecasting model, which approximates the gap between the fundamental equilibrium exchange rate and the actual exchange rate with the long-maturity forward exchange rate. Our out-of-sample forecasting results for major currencies are unprecedented. The forecasting model is simple, easy to replicate, and the data we use are available in real time and not subject to revisions.